ANALISIS EFEKTIVITAS PLTS ATAP (ROOFTOP) UNTUK MENGURANGI TAGIHAN LISTRIK RUMAH TANGGA: Analisis Efektivitas PLTS Atap (Rooftop) Untuk Mengurangi Tagihan Listrik Bangunan - Edo Prasetio (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
The rising cost of electricity due to the dependence on fossil fuels has become a significant burden for households in Indonesia. Rooftop Solar Power Systems (PLTS Atap) emerge as a potential clean energy solution to address this problem. This study aims to analyze the effectiveness and economic feasibility of implementing Rooftop Solar as an effort to reduce household electricity bills. This study applies a mixed-method (quantitative-qualitative) approach through surveys and interviews with 25 households with 1300 VA or higher electricity service. The quantitative analysis results show that for an average monthly consumption of 329.1 kWh, a 3 kWp solar power system is highly recommended. This system has the potential to cut monthly bills by up to 95.7% with a payback period of approximately 8.5 years, although it requires an initial investment of around IDR 46,250,000. However, the qualitative findings reveal that the majority of respondents (56%) are hesitant due to this initial investment cost. Meanwhile, another 20% of respondents were neutral, indicating a need for more information and accessible financing schemes. This study concludes that although Rooftop Solar is highly feasible from a technical and economic standpoint, its main barriers are socio-economic. The success of future adoption heavily depends on the availability of accessible financing models to overcome the initial capital challenge.